The Present and the Future of Infringement Proceedings: Lessons learned from Kavala v Türkiye - Çalı, Başak (European Human Rights Law Review, 2023)
The Council of Europe is headed to its 4th Summit under the shadow, most likely, of the unimplemented infringement proceedings judgment in the case of Kavala v Turkey . The aim of this article is to investigate what this persistent non-implementation teaches us for the present as well as for the future reform of infringement proceedings monitoring. Strengthening this is of inestimable importance for the future credibility of the Council of Europe, as well as the authority of the European Court of Human Rights (ECtHR) in general. The lack of a clear strategy for handling non-implementation of infringement proceedings will have a dissuasive effect on the further use of such proceedings by the Committee of Ministers, it removes any teeth proceedings were ever intended to have. In this article I argue that the future of the effective monitoring of judgments resulting from infringement proceedings depends on: (a) the foreseeable proceduralisation of the mechanisms to exert pressure on non-implementing states; and (b) further judicialisation of the ECtHR’s handling of the remedies required to implement judgments resulting from infringement proceedings. In conclusion, I reflect on possible objections to this double call of proceduralisation and judicialisation as the basis of reform.
CRIS-Team Scopus Importer:2024-06-28
Keywords: Enforcement; European Court of Human Rights; Fines; Human rights; Judgments and orders; Penalties